Sosialisasi Digitalisasi UMKM Dalam Menunjang Keuangan Inklusif - Yefriza; Pasaribu, Esti; Rospida, Lela; Sitorus, Antoni; Putri, Novi Tri (Kreativasi : Journal of Community Empowerment, 2025)
One of the Indonesian government's efforts is to develop Micro, Small, and Medium Enterprises, usually MSMEs, to restore economic stability and encourage economic growth and national economic recovery. A common problem for every MSME is that knowledge about financial reports is still weak. Based on these conditions, the community service team for the Master of Applied Economics, Faculty of Economics and Business, Bengkulu University, held socialization activities for MSME Digitalization Development in Pekik Nyering Village, Central Bengkulu Regency and made this an effort to increase the competitiveness of MSME products. The socialization focused on training in making simple financial reports and using the SIAPIK application to make it easier to record financial transactions precisely and practically anytime, anywhere, without carrying a cash book. The activity was carried out on September 4, 2024, and was well received by the people of Pekik Nyering Village. After training, MSMEs can use the SIAPIK application and are expected to continue using this application on an ongoing basis.